Relationship between education and cognitive performance among healthy Malay adults - A.I.Z. Amir Hamzah,; Z.H. Abu Bakar,; N.F. Abdul Sani,; Tan, J-K.; Mohd Hanafi Ahmad Damanhuri,; K.N. Nor Aripin,; M.D. Mohd Rani,; N.A. Noh,; Rosdinom Razali,; Mizhanim Mohamad Shahimin,; S. Makpol,; M. Mazlan,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Higher level of education is associated with better cognitive performance and lower risk of developing dementia. However, the effect of education on cognitive performance varies across different cognitive domains and in different populations. The aim of this study was to determine the relationship between education and performance of different cognitive domains among healthy Malay adults. A total of 53 individuals aged 29 to 77 years participated in a battery of neurophysiological tests consisting of Mini-Mental State Examination, Montreal Cognitive Assessment, digit span, visual reproduction and digit symbol speed test (DSST). Blood test was performed for each participant to obtain their biochemical profile. Educational level was divided into level 1 (PMR), level 2 (SPM), level 3 (STPM), level 4 (Diploma) and level 5 (Degree). Simple linear regression indicated that years of education was positively associated with scores of delayed visual reproduction (b=1.348, p=0.002) and DSST (b=3.257, p=0.012). However, scores of all the tests were not significantly different among different levels of education after controlling for age, gender and blood test profile by ANCOVA. Multiple linear regression analysis showed that MMSE score was associated with red cell distribution width (b=-0.628, p=0.005), age (b=-0.119, p<0.001) and there was interaction between high density lipoprotein (HDL) with age (b=0.047, p<001). MoCA score was associated with age (b=-0.121, p<0.001), gender (male compared to female, b=1.870, p=0.020) and HDL (b=1.681, p=0.047). Age was associated with backward digit span (b=-0098, p<0.001) and immediate visual reproduction (b=-0.348, p<0.001), resp. Delayed visual reproduction was associated with age (b=-0.323, p<0.001) and potassium level (b=-4.471, p=0.016). DSST was associated with age (b=-0.911, p<0.001) and alanine aminotransferase (b=-0.754, p=0.002). The lack of association between educational level and cognitive performance after adjusting for confounders in this study maybe due to multiple factors influencing cognitive performance and further studies with a larger sample size are needed to further identify the factors involved.